Prescription Pattern of Anti Microbial Agents in Patients of Appendicitis Admitted in Tertiary care Teaching Hospital: a Cross Sectional Study - Ghodki, Sarang; Borade, Sanjio; Bhore, Ashok; Umale, Narayan; Bansod, Kishor; Bijwe, Varsha (International Journal of Medical Research and Review, 2014)
Introduction: Appendicitis is one of the common conditions which usually require surgical intervention. It is almost always associated with inflammation with bacterial infection, treated either conservatively or surgically. In both situations, different types of antimicrobial agents (AMAs) are used. AMAs are used either in inadequate or over doses. This results in development of antimicrobial resistance in microorganisms and thereby increasing duration of stay, morbidity and cost of treatment. Objective: To Study the Prescription pattern of AMAs in patients of appendicitis admitted in Surgery ward of tertiary care teaching hospital. Method: It was a cross sectional study carried out over a period of six months. Data was collected from cases papers of surgery ward from medical record section. It was analyzed and evaluated on basis of various parameters like demographic distribution, complicated or uncomplicated cases, type of treatment, percentage of AMAs prescribed in order of preference, dose, duration, frequency and route of administration of AMAs (i.e. Rational use), average no. of AMAs per patient, incidence of surgical site infection, duration of stay in hospital, etc. Results: Out of 113 cases of appendicitis, only 33 (29.20%) were treated rationally. Ceftriaxone and cefpodoxime were most frequently used AMAs. Average AMAs prescribed per patient were 3. Average of total durationof stay in hospital was 10 days. Conclusion: AMA prescription policy should be formulated and displayed in surgery ward for complicated and uncomplicated appendicitis cases to promote / facilitate rational prescription.